2019
DOI: 10.4274/tjps.galenos.2018.12599
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Thiazolidone Scaffolds Using Pocket Modeling for Development of Potential Secretory System Inhibitors of <i>Mycobacterium tuberculosis</i>

Abstract: Amaç: Mycobacterium tuberculosis, son on yılda kanserden sonra en ölümcül hastalık olan tüberkülozun etkenidir. Çoklu ilaç ve ilaca dirençli suşların gelişimi, tüberküloz problemini daha da kritik kılmaktadır. Son 40 yılda, tedavi rejimine sadece bir molekül eklenmiştir. Genel olarak ilaç tasarım ve geliştirme programları, bakteri hücresi fonksiyonunda önemi olduğu bilinen proteinleri hedeflemektedir. M. tuberculosis, SecA2 ve ESX gibi özel protein ihracat sistemlerine sahiptir. Gereç ve Yöntemler: Bu çalışmad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Additionally, it was recently shown that the SecA2 pathway activates the ATK kinase checkpoint protein, resulting in the formation of double-strand breaks (DBSs) in host DNA [ 64 ]. Several compounds have been identified as potential inhibitors of Sec pathways, including analogs of the dye rose Bengal, thiouracil analogs and thiazolidine derivatives [ 65 , 66 , 67 ].…”
Section: Targeting the Secretory Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it was recently shown that the SecA2 pathway activates the ATK kinase checkpoint protein, resulting in the formation of double-strand breaks (DBSs) in host DNA [ 64 ]. Several compounds have been identified as potential inhibitors of Sec pathways, including analogs of the dye rose Bengal, thiouracil analogs and thiazolidine derivatives [ 65 , 66 , 67 ].…”
Section: Targeting the Secretory Systemsmentioning
confidence: 99%
“…Different thiazolidine derivatives (n.29, Table 5 ) were tested for anti-mycobacterial activity. Khare et al discovered Q30, M9, M26, U8, and R26 molecules as potent SecA2 inhibitors among 30 identified compounds [ 67 ]. These compounds have shown promising in vitro antimycobacterial activity and may open up a new path for the development of novel tuberculosis therapies.…”
Section: Targeting the Secretory Systemsmentioning
confidence: 99%